2006
DOI: 10.1091/mbc.e05-11-1043
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Mapping of DNA Synthesis in Saccharomyces cerevisiae Reveals That Mechanisms Preventing Reinitiation of DNA Replication Are Not Redundant

Abstract: To maintain genomic stability, reinitiation of eukaryotic DNA replication within a single cell cycle is blocked by multiple mechanisms that inactivate or remove replication proteins after G1 phase. Consistent with the prevailing notion that these mechanisms are redundant, we previously showed that simultaneous deregulation of three replication proteins, ORC, Cdc6, and Mcm2-7, was necessary to cause detectable bulk re-replication in G2/M phase in Saccharomyces cerevisiae. In this study, we used microarray compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(103 citation statements)
references
References 47 publications
10
92
1
Order By: Relevance
“…genes contributes to colorectal tumorigenesis. This could be linked to an increase in the number of active origins of replication (and therefore re-replication and aneuploidy), as already shown in yeast (Green et al, 2006).…”
Section: Discussionmentioning
confidence: 58%
“…genes contributes to colorectal tumorigenesis. This could be linked to an increase in the number of active origins of replication (and therefore re-replication and aneuploidy), as already shown in yeast (Green et al, 2006).…”
Section: Discussionmentioning
confidence: 58%
“…[13][14][15][16] The deregulation of any one pre-RC component is not sufficient to induce DNA re-replication. [14][15][16][17] The simultaneous deregulation of two components induces limited origin re-firing in a subset of origins, while deregulation of ORC, Cdc6, and the MCM2-7 complex together induces more substantial DNA re-replication. 14,16,17 The simultaneous deregulation of Cdt1 with the other three components has not been reported.…”
Section: The Prevention Of Dna Re-replication In Yeast and Metazoansmentioning
confidence: 99%
“…org/supplemental/). Recently, Green et al (2006) showed little or no replication initiation defects associated with ORC, MCM, and CDC6 mutations deregulating replication control by a microarray-based assay. Thus, overall we consider it unlikely that replication initiation defects contribute significantly to the results presented here.…”
Section: Clb6d3pmentioning
confidence: 99%
“…For these reasons, we consider that this DNA flow cytometry signal likely represents authentic rereplication, but we recognize that in borderline cases it is hard to be sure of this. Recently, Green et al (2006), using a microarray method, showed that rereplication at some specific loci could be detected even in cells without DNA flowcytometry-detectable rereplication, and such an assay may ultimately be necessary to definitively prove rereplication in cases that are borderline by DNA flow cytometry.…”
Section: Clb6d3pmentioning
confidence: 99%